Training Volume in Distance Running - Soulas, Δημήτρης; Grivas, Γεράσιμος; Voutselas, Βασίλης; Manou, Βασιλική; Papanikolaou, Ζήσης; Kritikos, Αλέξανδρος (Inquiries in Physical Education and Sport, 2010)
Training volume in middle and distance running events is one of the most important elements for improving performance that has not been adequately researched. The aim of the present study was to investigate the running distances (training volume) the athletes cover to improve aerobic and anaerobic performance during the yearly training periods. Data was collected through interviews and questionnaires administered to coaches. The results showed that middle distance runners (800m and 1500m) run 4703.7±1224.1 km, long distance runners (5000m, 10000m and 3000m steeple) run 5422±1206.41km and marathon runners run 5781.1±1634 km per year, while runners in the 1980s used to cover longer distances. This decrease in running volume is due to the different training methods coaches follow in our time.